2021
DOI: 10.1371/journal.pone.0261385
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of host response strategies to distinguish bacterial and viral infection

Abstract: Objectives Compare three host response strategies to distinguish bacterial and viral etiologies of acute respiratory illness (ARI). Methods In this observational cohort study, procalcitonin, a 3-protein panel (CRP, IP-10, TRAIL), and a host gene expression mRNA panel were measured in 286 subjects with ARI from four emergency departments. Multinomial logistic regression and leave-one-out cross validation were used to evaluate the protein and mRNA tests. Results The mRNA panel performed better than alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A bovine experimentally induced mastitis model would be ideal for these types of experiments for multiple reasons. In this model, features of infection may be altered based on the pathogen(s) introduced, allowing for the study of various host-pathogen dialogs that determine the nature of the immune response ( 124 , 125 ). Non-invasive read outs such as somatic cell count and bacterial load in milk can be used to follow the course of infection/treatment in real time.…”
Section: Discussionmentioning
confidence: 99%
“…A bovine experimentally induced mastitis model would be ideal for these types of experiments for multiple reasons. In this model, features of infection may be altered based on the pathogen(s) introduced, allowing for the study of various host-pathogen dialogs that determine the nature of the immune response ( 124 , 125 ). Non-invasive read outs such as somatic cell count and bacterial load in milk can be used to follow the course of infection/treatment in real time.…”
Section: Discussionmentioning
confidence: 99%
“…The test also worked equally well among participants with acute COVID-19. Although we did not assess the combined performance of the HR-B/V test and procalcitonin measurement, a previous study found no improvement vs HR-B/V testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the secondary outcomes will involve similar regression models, depending on the type of the outcome variable. In a further secondary analysis with IV antibiotic duration as the outcome, we will test the interaction between treatment arm and biomarker subgroups, categorised according to the following criteria: MR-proADM high (≄ 0.7 nmol/l) or low (< 0.7 nmol/l) [ 27 ], ImmunoXpert score high (> 0.65), intermediate, or low (< 0.35) [ 29 , 31 ]. PRECISE secondary analyses will not be performed if analysis of the same outcome in the host trial fails to discover a significant treatment effect.…”
Section: Sub-studiesmentioning
confidence: 99%